Evaluation and Optimization of Radiation Dose in Computed Tomography - Khudair, Zahraa Ali; Kattoof, Suzan Yassir; Mahmoud, Hassan Abbas; ali, Hajar sameer (American Journal of Botany and Bioengineering, 2025)
In computed tomography, patient radiation doses should be kept as low as possible in order to minimise the risk of that individual developing cancer in the future from the radiation from the scan. This message needs to be effectively but sensitively communicated to the lay public. The objective of this work was to understand the fundamentals of computed tomography (CT) radiation dose, how CT radiation doses are measured, and to discuss the factors influencing that dose, such that CT radiation dose can be evaluated and optimised. With the development of technology, the successive introduction of multi-slice spiral CT and cone beam CT scans has allowed the 3D high-resolution reconstruction of a broad anatomic region in a very short time (one rotation). This fact, coupled with the synthetic generation of very thin sections, has resulted in a large increase in the number of sections acquired per examination, namely with the new scanner models, which allow the acquisition of the about 800 sections typical of the chest, abdomen, and pelvis. Patient radiation dose is an important issue in modern CT imaging, considering the enormous increase in the number of examinations performed in the last two decades. On the 40th anniversary, it is important to remember that unlike other X-ray procedures, the average dose to which the population is exposed in CT examinations increases rather than decreases with time. For systemic cancer in children, it was recently noted that the risk was about 1% per average dose of 10 mSv in the first decade of life without a clear dose-response relationship.